Measurement of health system performance at district level: A study protocol - Atul Sharma; Shankar Prinja; Arun Kumar Aggarwal (SAGE Publishing, 2018)
Background: Limited efforts have been observed in low and middle income countries to undertake health system performance assessment at district level. Absence of a comprehensive data collection tool and lack of a standardised single summary measure defining overall performance are some of the main problems. Present study has been undertaken to develop a summary composite health system performance index at district level. Methods: A broad range of indicators covering all six domains as per building block framework were finalized by an expert panel. The domains were classified into twenty sub-domains, with 70 input and process indicators to measure performance. Seven sub-domains for assessing health system outputs and outcomes were identified, with a total of 28 indicators. Districts in Haryana state from north India were selected for the study. Primary and secondary data will be collected from 378 health facilities, district and state health directorate headquarters. Indicators will be normalized, aggregated to generate composite performance index at district level. Domain specific scores will present the quality of individual building block domains in the public health system. Robustness of the results will be checked using sensitivity analysis. Expected impact for public health: The study presents a methodology for comprehensive assessment of all health system domains on basis of input, process, output and outcome indicators which has never been reported from India. Generation of this index will help identify policy and implementation areas of concern and point towards potential solutions. Results may also help understand relationships between individual building blocks and their sub-components.